Analysis of CBCS publications for Open Access, data availability statements and persistent identifiers for supplementary data - Kieselbach, Th. Theresa (Umeå University, 2023)
General description

This dataset contains some markers of Open Science in the publications of the Chemical Biology Consortium Sweden (CBCS) between 2010 and July 2023. The sample of CBCS publications during this period consists of 188 articles. Every publication was visited manually at its DOI URL to answer the following questions.

1. Is the research article an Open Access publication?

2. Does the research article have a Creative Common license or a similar license?

3. Does the research article contain a data availability statement?

4. Did the authors submit data of their study to a repository such as EMBL, Genbank, Protein Data Bank PDB, Cambridge Crystallographic Data Centre CCDC, Dryad or a similar repository?

5. Does the research article contain supplementary data?

6. Do the supplementary data have a persistent identifier that makes them citable as a defined research output?

Variables

The data were compiled in a Microsoft Excel 365 document that includes the following variables.

1. DOI URL of research article

2. Year of publication

3. Research article published with Open Access

4. License for research article

5. Data availability statement in article

6. Supplementary data added to article

7. Persistent identifier for supplementary data

8. Authors submitted data to NCBI or EMBL or PDB or Dryad or CCDC

Visualization

Parts of the data were visualized in two figures as bar diagrams using Microsoft Excel 365. The first figure displays the number of publications during a year, the number of publications that is published with open access and the number of publications that contain a data availability statement (Figure 1). The second figure shows the number of publication sper year and how many publications contain supplementary data. This figure also shows how many of the supplementary datasets have a persistent identifier (Figure 2).

File formats and software

The file formats used in this dataset are:

.csv (Text file)
.docx (Microsoft Word 365 file)
.jpg (JPEG image file)
.pdf/A (Portable Document Format for archiving)
.png (Portable Network Graphics image file)
.pptx (Microsoft Power Point 365 file)
.txt (Text file)
.xlsx (Microsoft Excel 365 file)

All files can be opened with Microsoft Office 365 and work likely also with the older versions Office 2019 and 2016.

MD5 checksums

Here is a list of all files of this dataset and of their MD5 checksums.

1. Readme.txt (MD5: 795f171be340c13d78ba8608dafb3e76)
2. Manifest.txt (MD5: 46787888019a87bb9d897effdf719b71)
3. Materials_and_methods.docx (MD5: 0eedaebf5c88982896bd1e0fe57849c2),
4. Materials_and_methods.pdf (MD5: d314bf2bdff866f827741d7a746f063b),
5. Materials_and_methods.txt (MD5: 26e7319de89285fc5c1a503d0b01d08a),
6. CBCS_publications_until_date_2023_07_05.xlsx (MD5: 532fec0bd177844ac0410b98de13ca7c),
7. CBCS_publications_until_date_2023_07_05.csv (MD5: 2580410623f79959c488fdfefe8b4c7b),
8. Data_from_CBCS_publications_until_date_2023_07_05_obtained_by_manual_collection.xlsx (MD5: 9c67dd84a6b56a45e1f50a28419930e5),
9. Data_from_CBCS_publications_until_date_2023_07_05_obtained_by_manual_collection.csv (MD5: fb3ac69476bfc57a8adc734b4d48ea2b),
10. Aggregated_data_from_CBCS_publications_until_2023_07_05.xlsx (MD5: 6b6cbf3b9617fa8960ff15834869f793),
11. Aggregated_data_from_CBCS_publications_until_2023_07_05.csv (MD5: b2b8dd36ba86629ed455ae5ad2489d6e),
12. Figure_1_CBCS_publications_until_2023_07_05_Open_Access_and_data_availablitiy_statement.xlsx (MD5: 9c0422cf1bbd63ac0709324cb128410e),
13. Figure_1.pptx (MD5: 55a1d12b2a9a81dca4bb7f333002f7fe),
14. Image_of_figure_1.jpg (MD5: 5179f69297fbbf2eaaf7b641784617d7),
15. Image_of_figure_1.png (MD5: 8ec94efc07417d69115200529b359698),
16. Figure_2_CBCS_publications_until_2023_07_05_supplementary_data_and_PID_for_supplementary_data.xlsx (MD5: f5f0d6e4218e390169c7409870227a0a),
17. Figure_2.pptx (MD5: 0fd4c622dc0474549df88cf37d0e9d72),
18. Image_of_figure_2.jpg (MD5: c6c68b63b7320597b239316a1c15e00d),
19. Image_of_figure_2.png (MD5: 24413cc7d292f468bec0ac60cbaa7809)
Keywords: Open access; Organisation of information and knowledge resources; Medical and Health Sciences; Medicin och hälsovetenskap